ANALYSIS OF HOTS IN ENGLISH TEACHER-MADE TEST - Junitri Dian Syahdanis; Dedi Sofyan; Wisma Yunita (BASIS (Bahasa dan Sastra Inggris), 2021)
HOTS were three upper cognitive processes of Bloom's revised taxonomy by Anderson and Krathwohl (2001) which consisted of analyzing, evaluating, and creating. The objectives of this research were (1) to know the distribution of HOTS in English teacher-made test (2) to evaluate the relevancy of the English teacher-made test with the competencies in English simplified syllabus; (3) to know the reason for less appearance of HOTS in the English teacher-made test. This research focused on English teacher-made tests for grade X and grade XI in the academic year of 2020/2021 at the senior high school number 6 and senior high school number 11 in Bengkulu city. This study adopted a mixed-method as the research design. The first result displayed that HOTS obtained lower distribution rather than LOTS and MOTS in English teacher-made tests for grade X and grade XI at both schools. The second result showed that the English teacher-made tests for grade X and grade XI at both schools were relevant to the English simplified syllabus. The last, the reason for less appearance of HOTS in English teacher-made test at both schools came from two aspects. From the teachers' aspect, they needed more HOTS professional training to improve their understanding of HOTS. From the students' aspect, they needed to practice and learn more about HOTS questions, because most students could not work with HOTS questions.